Immunogenicity evaluation of altSonflex1-2–3 Shigella vaccine across mice, rats, and rabbits to inform human translational insights - Caradonna, Valentina; Alfini, Renzo; Pinto, Marika; Di Benedetto, Roberta; Giannelli, Carlo; Medaglini, Donata; Pettini, Elena; Iturriza, Miren; Rossi, Omar; Micoli, Francesca; Mancini, Francesca (Frontiers in Immunology, 2026)
Shigella, a leading cause of bacillary dysentery, represents a significant global health challenge, particularly in low- and middle-income countries. Shigellosis predominantly affects children under the age of five and is associated with high morbidity and mortality rates. To address this burden, a generalized modules for membrane antigens (GMMA)-based vaccine, altSonflex1-2-3, incorporating S. sonnei and S. flexneri 1b, 2a, and 3a O-antigens, has been developed. This study aimed to evaluate and compare the immunogenicity of the altSonflex1-2–3 vaccine in mice, rats, and rabbits. Significant increase in O-antigen specific IgG response was observed in all animal models after one single injection, that further increased post-second vaccination in mice and rats for all antigens at all tested doses. In rabbits, booster effects were observed for all antigens, except for S. flexneri O-antigen at the highest dose and S. sonnei O-antigen at intermediate and high dose. This study showed how each species exhibited its own unique dose-response pattern against S. flexneri 1b and 3a. Instead, S. flexneri 2a consistently showed a positive dose-response in every model examined. A hook effect was observed for S. sonnei IgG across all models, with responses peaking at medium doses and decreasing at higher doses. This trend was most pronounced in mice and less evident in rats. Across all antigens, mice and rabbits exhibited more homogeneous immune responses to the 4 antigens, while rats showed numerically higher response to S. sonnei and S. flexneri 2a compared to S. flexneri 1b and 3a. Interestingly, this pattern in rats aligns more closely with responses recently observed in European adults. The vaccine has now advanced to Phase 2 clinical trials in the target population of 9-month-old infants, where different doses of the vaccine are being tested. Immune data collected will allow to further evaluate which preclinical model can better predict humoral response elicited in different age group populations. Expanding studies of this kind across different platforms and pathogens could provide valuable insights into the optimal animal models for supporting rapid vaccine design and development prior to clinical trials.